THE GROUTH OF TOURIST IN RAJASTHAN TOURISM - Parul (Innovative Research Thoughts, 2017)
Rajasthan is the land of kings and warriors and is famous for its heritage, art, craft and culture. The state is famous for its kindness also. Rajasthan is a grouping of all the tourism products. Overseas tourists and domestic tourists both can take pleasure in whatever they aspiration and whatever they wait for from a tourist goal. The state represent an abnormal variety in all its form, be it, people, culture, ethnicity, costume, cuisine, dialect and melody. No other district in the country assembles the many paradox of India, as does the barren region land of Rajasthan. unforeseen forest glens, lakes and temples come into view like mirages in the deserts. There is anecdote in Rajasthan’s forts and palaces and arts of heroism retold in ballads and folklore. Then there are sanctuaries sheltering the rich and wide-ranging variety of vegetation and fauna. And the sparkling Thar Desert belt trinkets with a rare and startling prospect. Rajasthan has the whole thing for every age group of tourists. The visitor can vacation the state with the purpose of knowledge, enjoyment, relaxation, medical, wedding, adventure, sports, cultural, pilgrimage and now a days with the purpose of MICE and literacy tourism. The paper is an attempt to find out the satisfaction level of Foreign and Domestic Tourists who have visited Rajasthan. The paper also focuses of Rajasthan Tourism.